Surface spectroscopy and structural analysis of nanostructured multifunctional (Zn, Al) layered double hydroxides. (13th April 2016) - Richetta, M.; Digiamberardino, L.; Mattoccia, A.; Medaglia, P. G.; Montanari, R.; Pizzoferrato, R.; Scarpellini, D.; Varone, A.; Kaciulis, S.; Mezzi, A.; Soltani, P.; Orsini, A.
Abstract : Two types of (Zn, Al) layered double hydroxide were prepared by a hydrothermal process at room temperature using Zn salt precursors on Al foils. The examined LDHs differ for the hosted anions in the interlamellar space, namely Cl − and NO3 − . Scanning electron microscopy, X‐ray photoelectron spectroscopy and ultraviolet photoemission spectroscopy have been used to characterize four types of the samples, representative of the two hosted anions (Cl − and NO3 − ) and two times of growth (6 and 24 h). X‐ray photoelectron spectroscopy results permitted to describe the interactions between inorganic anions hosted in the interlamellar space and the metallic cations on the brucite layer. They also allowed giving a tentative explanation of the different morphologies observed by scanning electron microscopy. Copyright © 2016 The Authors Surface and Interface Analysis Published by John Wiley & Sons Ltd.